Assesment On The Cytotoxicity, Apoptosis And Autophagy Properties Of Chemically Synthesised Silver Nanoparticles On Beas 2b Cells - Mohd Raflee, Nur Afiqah (2017)

(untitled)
Silver nanoparticles (AgNPs) has been shown to exhibit anti- microbial effect. The exploitation of AgNPs has emerged in the recent years and may trigger major health problem